2011
DOI: 10.1128/iai.05666-11
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Computational Genetic Analysis: Multiple Complement Alleles Control Survival after Candida albicans Infection

Abstract: Candida albicans is a fungal pathogen that causes severe disseminated infections that can be lethal in immunocompromised patients. Genetic factors are known to alter the initial susceptibility to and severity of C. albicans infection. We developed a next-generation computational genetic mapping program with advanced features to identify genetic factors affecting survival in a murine genetic model of hematogenous C. albicans infection. This computational tool was used to analyze the median survival data after i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 62 publications
0
35
0
1
Order By: Relevance
“…Haplotype-based computational genetic mapping (HBCGM) was conducted as described previously [53], and used to identify those genomic regions whose genetic variation pattern was correlated with input phenotypic values for the 23 inbred strains utilized in these studies.…”
Section: Methodsmentioning
confidence: 99%
“…Haplotype-based computational genetic mapping (HBCGM) was conducted as described previously [53], and used to identify those genomic regions whose genetic variation pattern was correlated with input phenotypic values for the 23 inbred strains utilized in these studies.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the relatively robust fungal cell wall it appears unlikely that the membrane attack complex affects Candida viability; however, complement-mediated opsonization enhances phagocytosis of fungal cells and killing by macrophages and neutrophils (reviewed in Rambach & Speth, 2009). The relevance of complement for the antiCandida response has been clearly demonstrated in mice, where strains with complement defects show a higher susceptibility to systemic candidiasis (Ashman et al, 2003;Mullick et al, 2004;Peltz et al, 2011;Tsoni et al, 2009). Like many bacterial pathogens, C. albicans has developed several mechanisms to interfere with complement activation (recently reviewed in Cheng, Joosten, Kullberg, & Netea, 2012;Luo, Skerka, Kurzai, & Zipfel, 2013).…”
Section: Humoral Defenses: Antimicrobial Peptides and Complementmentioning
confidence: 98%
“…It was also demonstrated that C5-deficient mice are more susceptible to systemic C. albicans infection, resulting in a higher fungal burden in the organs (73). A recent study using computational analysis proposed that different combinations of C5 and C1r/s alleles can predict the survival of different mouse strains in the systemic Candida infection model (86). This implies that reduced C1 deposition in the susceptible mice resulted in reduced C5 binding and activation.…”
Section: Soluble Factorsmentioning
confidence: 99%